Controversies in cerebrovascular disease: high or low doses of recombinant tissue plasminogen activator to treat acute stroke? A literature review - Montalván Ayala, V. (2022)
Introduction: The use of low doses of recombinant tissue plasminogen activator (rt-PA) was initially proposed in Asian countries in response to racial peculiarities related to the functionality of fibrinogen and coagulation factors that potentially increased the risk of intracerebral haemorrhage, and with a view to saving costs. In view of the controversy over the use of rt-PA below the standard dose, we conducted a literature review of studies promoting the use of low doses or comparing different doses of rt-PA. Development: We reviewed 198 abstracts related to the search terms and the full texts of 52 studies published in the last 30 years. We finally included 13 randomised clinical trials aiming to determine the efficacy and safety of the use of rt-PA at different doses in acute stroke, 14 observational cohort studies, 5 meta-analyses, and 3 systematic reviews. Conclusions: There is insufficient evidence to classify low doses of rt-PA as superior or at least not inferior to the standard treatment in the management of acute stroke in western populations. More clinical trials are required to determine whether the use of low doses is beneficial in patients with relative contraindications for thrombolytic therapy or other particular circumstances that may increase the risk of intracerebral haemorrhage.